Fibroblast Growth Factor 21-Null Mice Do Not Exhibit an Impaired Response to Fasting - Antonellis, Patrick Joseph; Hayes, Meghan Patricia; Adams, Andrew Charles (Frontiers in Endocrinology, 2016)
Fibroblast growth factor 21 (FGF21) is a pleotropic metabolic regulator, expression of which is elevated during fasting. To this end, the precise role played by FGF21 in the biology of fasting has been the subject of several recent studies, which have demonstrated contributions to the regulation of both lipid and carbohydrate metabolism. In the present study, we compared wild-type (WT) and FGF21-null (FGF21KO) mice, demonstrating that, despite the significant induction of FGF21 during fasting in the WT animals, our strain of FGF21-null mice exhibits only limited impairments in their adaptation to nutrient deprivation. Specifically, fasted FGF21KO mice display a mild attenuation of gluconeogenic transcriptional induction in the liver accompanied by partially blunted glucose production in response to a pyruvate challenge. Furthermore, FGF21KO mice displayed only minor impairments in lipid metabolism in the fasted state, limited to accumulation of hepatic triglycerides and a reduction in expression of genes associated with fatty acid oxidation. To address the possibility of compensation to germline deletion of FGF21, we further interrogated the role of endogenous FGF21 via acute pharmacological blockade of FGF21 signaling. At the transcriptional level, we show that FGF21 signaling is required for full induction of gluconeogenic and oxidative genes in the liver. However, corroborating our findings in FGF21KO mice, pharmacological blockade of the FGF21 axis did not profoundly disrupt the physiological response to fasting. Taken as a whole, these data demonstrate that, while FGF21 is partially required for appropriate gene expression during the fed to fasted transition, its absence does not significantly impact the downstream physiology of the fasted state.